Sport and well-being: Frequency of physical activity and life satisfaction - Ade Hermawansyah; Sumaryanto; Elsa Ariestika; I Putu Agus Dharma Hita (UIR Press, 2021)
Living a better and happy life (well-being) is a key point for people’s daily life. Well-being integrates both of physical and psychological health namely feelings, emotions, and life satisfaction. This means that good life is when people are physically fit and they are satisfied with their life. There have been few studies investigating the relationship between physical activity and life satisfaction in Indonesia. Therefore, this quantitative study is aimed to examine the association between sport and well-being, especially the frequency of physical activity and life satisfaction. The data used are from the fifth wave of the Indonesian Family Life Survey (IFLS) 2014, with 31,669 participants from 15,160 households and 297 districts in Indonesia. Linear regression is used for data analysis, adjusting for control variables. The results show that the more frequent people exercise, the more they are satisfied with their lives, even after controlling for a set of confounding variables. Different measures need to be taken to increase physical activity as parts of people’s daily life in order to protect their health and enjoy a better life.